Literacy Questions Based on Hots Using Context Covid-19 - Puspitasari, Linda; Alwi, Zahra; Suhardi, Suhardi; Zulkardi, Zulkardi (Journal of Education Reseach and Evaluation, 2021)
The emergence of problems in HOTS-based literacy is due to the teacher's lack of understanding in developing questions. Teachers must prepare students who can integrate 21st-century skills into their learning process. The average PISA 2018 score experienced a decline in three competency areas with the most significant reduction in reading. It will have an impact on the low ability of students. This research aims to develop questions based on Higher Order Thinking Skills (HOTS). This type of research is development. The method used in this research is research and development. The data collection used is literature study techniques, questionnaires, focus group discussions, and one-to-one tests. The data obtained from the study are in the form of curriculum reviews and literature related to PISA, reasoning, HOTS questions, and digital learning media in the format of websites/youtube. The data obtained from interviews, questionnaires, and group discussions focused on qualitative and quantitative descriptive. The result of the research is that the prototype produced 1 HOTS-based literacy question that follows the PISA standard. High-ability students answered question number 6, got 9. Students with moderate ability responded to questions number 6 and 10, got a score of 8. Low-ability students who responded to questions number 4 and 10 got a score of 8. The average score obtained by three students (from the high group, medium, and low) was 83.3. They were included in the very good category based on the criteria given in the method section. It can be said that HOTS-based literacy can improve students' abilities.